Décentralisation en République Démocratique du Congo (RDC/DRC) et faible contribution des entités territoriales décentralisées à la gouvernance et au développement local : étude menée dans les Chefferies et Secteurs de l’Ituri - Kasemengo, Théodard Wahangire (IJRDO - Journal of Business Management, 2020)
The democrat Republic of Congo, second country in Africa by its size (2.345.410 km2) after Algeria (2.381740 km2) deserves to be managed  by three poles including the central government that of provinces and territorial entities decentralized from this perspectives, decentralization becomes the governance that reapproach the governors to the ruled. To achieve this, several reforms have been undertaken for several decades including the years 1982 in order to boost local development. Paradoxically in practice, decentralized territorial entities are characterized in particular by authoritarian management, amateurism, nepotism, the squandering of public resources testifying the deficit of governance.Most of the centralized territorial entities of the DRC are stuck at this reality, especially the chiefdoms and sectors of the province of Ituri. The animators of the chiefdoms and sectors of this province manage like many other territorial entities decentralized in DRC the public resources in violation of the laws of the relating to the distribution of the administrative and fiscal powers of the decentralized territorial entities, the provinces and central power.This result in the absence and deterioration of basic infrastructure: buildings of local public administration, school, hospitals and health centers, agricultural feeder roads that result in a small contribution of these entities to local development.The combination of the resources in data collection of the direct observation called uncommitted, the directive interview with resources persons and the analysis of contents taking into account realities of ground proves that said entities are mismanaged.The causes blocking this development resources being related to the authoritarian decentralization mode of management, followed by the economic and social ones justify that it is more than necessary that the democratic decentralization be implemented through the credible elections of these animators and strict respect of the principles affecting, so that the governance of these entities is improved to allow this mode of management to drive local development. The combination of decentralization, governance and local development is the keystone of any decentralizing reform in the DRC to achieve the objective.